2018
DOI: 10.1007/s00737-018-0893-3
|View full text |Cite
|
Sign up to set email alerts
|

A population survey of prevalence rates of antenatal depression in the Irish obstetric services using the Edinburgh Postnatal Depression Scale (EPDS)

Abstract: Ireland has the second-highest birth rate in Europe and poorly developed perinatal psychiatry services. There are no screening services for antenatal depression and no data available on prevalence rates of depression among women attending the Irish obstetric services. The aim of this study was to assess the prevalence rates of depression during pregnancy in a population sample in Ireland using the Edinburgh Postnatal Depression Scale (EPDS) as a screening tool. Pregnant women during all stages of pregnancy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 43 publications
0
27
2
3
Order By: Relevance
“…The incidence of antenatal depression in our study was significantly lower than that reported in low-and middle-income areas, such as Africa, where the incidence was 26.3% [6] , but the prevalence reported in our study might be slightly higher than that reported in high-income countries, such as Ireland [28] . This discrepancy in prevalence between countries might be due to the differences in depression screening tool, culture, study methodology, study population, socio-economic and socio-demographic variations.…”
Section: Discussioncontrasting
confidence: 87%
“…The incidence of antenatal depression in our study was significantly lower than that reported in low-and middle-income areas, such as Africa, where the incidence was 26.3% [6] , but the prevalence reported in our study might be slightly higher than that reported in high-income countries, such as Ireland [28] . This discrepancy in prevalence between countries might be due to the differences in depression screening tool, culture, study methodology, study population, socio-economic and socio-demographic variations.…”
Section: Discussioncontrasting
confidence: 87%
“…Consistent with previous studies (Silverman et al, ), among women with no depression history, younger age was associated with increased risk of depressive symptoms, even though the young women were generally prepared for their forthcoming delivery. However, because of their youth and the frightening delivery experience, young women are relatively likely to experience severe depression (Jairaj et al, ; Melville, Gavin, Guo, Fan, & Katon, ). Moreover, compared with 26‐34‐year‐old women (reference group), older women (≥35 years old) were more likely to belong to Classes 3 and 4, which were associated with the presence of physio‐somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of non-pregnant women of reproductive age, low levels of education increased the risk of depression (Nguyen, Weiss, Beydoun, & Kancherla, 2017). Education can increase knowledge of the details of gestation and delivery and thereby reduce fear of childbirth and the risk of perinatal depression (Jairaj et al, 2018;Marcus, Flynn, Blow, & Barry, 2003).…”
Section: Demographics and Perinatal Characteristics Associated Withmentioning
confidence: 99%
“…A nationally representative household survey reports 32% of females and 18% of males having experienced sexual violence, while 66% of females and 73% of males experienced physical violence [19]. In other LMIC, the prevalence of antenatal depression ranges from 18% to 25% [20][21][22], while that in high-income countries is much lower and spans 6% to 16% [23,24]. A study in South Africa found that maternal childhood trauma predicted greater maternal depressive symptoms and more negative child outcomes within the first six months post-partum [25].…”
Section: Introductionmentioning
confidence: 99%